Efficacy and Biological Activity of Imatinib in Metastatic Dermatofibrosarcoma Protuberans (DFSP) - Silvia Stacchiotti; Maria A. Pantaleo; Tiziana Negri; Annalisa Astolfi; Marcella Tazzari; Gian Paolo Dagrada; Milena Urbini; Valentina Indio; Roberta Maestro; Alessandro Gronchi; Marco Fiore; Angelo Paolo Dei Tos; et al. (2015)
To report on imatinib mesylate (IM) in patients with metastatic dermatofibrosarcoma protuberans (DFSP)/fibrosarcomatous (FS)-DFSP and on the impact of the treatment on tumor biology.Ten consecutive patients treated with IM from 2007 to 2015 for a metastatic relapse from DFSP/FS-DFSP were identified. FISH analysis for COL1A1-PDGFB was performed. Two IM-treated and 4 naïve FS-DFSP were transcriptionally profiled by RNAseq on HiScanSQ platform. Differential gene expression was analyzed with edgeR (Bioconductor), followed by hierarchical clustering and Principal Component Analysis.All cases featured fibrosarcomatous in the metastasis and retained the COL1A1-PDGFB. Best RECIST response was: 8 partial response, 1 stable disease, and 1 progressive disease. Median progression-free survival was 11 months. Five patients received surgery after IM and all relapsed. IM was restored in 4 patients with a new response. After IM, the most upregulated genes included those encoding for immunoglobulins and those affecting functions and differentiation of endothelial cells. Pathway enrichment analysis revealed upregulation in genes involved in antigen processing and presentation, natural killer-mediated cytotoxicity, and drug and xenobiotics metabolism. Conversely, a significant down-regulation of kinase signaling pathways was detected.All metastatic cases were fibrosarcomatous. Most patients responded to IM, but PFS was shorter than reported in published series which included both DFSP and FS-DFSP. All patients operated after IM had a relapse, suggesting that IM cannot eradicate metastatic cases and that the role of surgery is limited. Transcriptional profile of naïve and posttreatment samples pointed the contribution of immune infiltrates in sustaining the response to IM.